Menstrual Hygiene Material Management: A Comparative Study of Knowledge and Practice among Different Age Groups of Women - Bhandari, Upama (KMC Research Journal, 2025)
Menstrual hygiene material management (MHMM) is vital for the physical, mental and social health and well-being of women, yet knowledge and practice levels vary across different age groups. The objective of this study was to study explores age-related differences in knowledge and practices of MHMM among women aged reproductive age (15–45) in Thaha Municipality, Nepal. This study seeks to answer the following questions: Is there a statistically significant difference in the knowledge level of menstrual hygiene material management among different age groups? and is there a statistically significant difference in the practice level of menstrual hygiene material management among different age groups? To explore these questions, out of a total of 12 wards of Thaha Municipality, wards 3, 5 and 7 were selected through cluster sampling method. Due to resource, material and time constraints, all women found in households aged 15 to 49 years were purposively selected. For this, data were obtained from 82 women using closed-ended questionnaire instruments regarding knowledge and practice related to menstrual hygiene material management. Data were analyzed by frequency table, mean comparison, standard deviation and one-way ANOVA with comparative means using SPSS version 27. The data were analyzed using ANOVA in SPSS (version 27). The findings show very significant differences in age on the knowledge of menstrual hygiene material management (p = 0.001) but no significant difference was found in Practice of MHMM (p = 0.280) among different age groups, with the 26–35 age group demonstrating higher awareness and practical engagement. The results suggest a need for age-specific interventions to promote effective MHMM strategies and policies.